BIBLIOMETRIC ANALYSIS OF THE IMPACTS OF CLIMATE CHANGE ON PHOTOVOLTAIC ENERGY PRODUCTION - Matheus da Fonseca Tinoco de Souza Araújo, Nícolas; Abrahão, Raphael (Revista de Engenharia Térmica, 2024)
Higher concentrations of greenhouse gases, resulting from anthropogenic actions associated with energy generation, are one of the causes of climate change. In view of this, several efforts have been undertaken in the search for more sustainable alternatives, and photovoltaic (PV) technology has stood out among the different possibilities. However, PV generation is highly sensitive to future climate variability, which is a source of uncertainty that can complicate energy planning and compromise the viability of systems. This theme has received attention from the academic community, but some challenges to mapping and identifying the relevant literature have been encountered. Therefore, this study was conducted to analyze and identify relevant aspects of international scientific production focused on the impacts of climate change on the potential of photovoltaic production, CC-PVP, through bibliometric techniques. For this purpose, 3900 articles from the Web of Science and Scopus databases, published between 1960 and 2021, were retrieved and analyzed through a bibliometric approach, using the SciMAT v1.1.04 tool. Among the results obtained, it is worth pointing out that the CC-PVP research field has moderate maturity, and it is concentrated in the areas of energy, fuels, and technology, as well as environmental sciences and meteorology. It was concluded that key themes revolve around global energy, forecasting photovoltaic energy production, and electrical energy consumption, especially concerning climate change. Furthermore, it was found that researchers from China, North America, and Australia contribute significantly to this area compared to researchers from other countries.